Between Veneration and Destruction: The Venus of St. Matthias: Perspectives from the Comparative Study of Religion - Radermacher, Martin (Entangled Religions, 2023)
This article discusses the so-called “Venus of St. Matthias,” a former Roman statue of the goddess Venus that has, throughout its history, been embedded in diverse contexts of use. It has been venerated, criticized, rejected, and (almost) destroyed until it found its way into a museum where it is kept to this day. Outlining some of the central stages of this history, the paper intends to illustrate and discuss some of the various types of anti-iconism as outlined in the introduction to this special issue. The object serves as a promising case to elaborate on the possible relations of religion and images and is a good example to explain the heterogenous constellations of iconic and anti-iconic attitudes towards specific objects. The Venus of St. Matthias has been entangled with both iconic and anti-iconic discourse, thus producing a narrative that is inextricably linked with its material substance.